Written Approval for Commercialization of Portrai Photography: A Study of Law No. 28 of 2014 in the context of Improving the Distro Business in Indonesia - Evi Retno Wulan (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of this research is to examine the rules of written approval for the Commercialization of Portrait Photography as contained in Article 12 Paragraph (1) of the Copyright Law No. 28 of 2014 in the context of Improving the Distro Business in Indonesia. Design/methodology/approach: The type of legal research used is normative juridical research. The approach used in this research is the statutory approach and the conceptual approach. The sources of legal materials used in this doctrinal research consist of primary legal materials and secondary legal materials. The collected legal materials will be analyzed in a qualitative normative manner by reviewing, interpreting, and constructing statements contained in in-laws and regulations and other legal documents related to issues related to photo commercialization. Findings: Given the increasing competition in the business world, many creative business actors make their productions interesting, one of which is done by making t-shirts with portraits of artists and public figures obtained from the photographer who took the photo shoot. For example, example, a photographer takes a photo of an artist and uses it to line up his photo studio by making advertisements or billboards for the artist's portrait in his photo studio and has obtained permission from the artist, then the photographer sells the results of his work to the person, who by that person takes the portrait of the artist in the photo. fit on t-shirts to produce and sell. In this case, the photographer and the person who bought the photographer's portrait (portrait photography) violated copyright because the commercialization of portrait photography contained in the t-shirt was carried out without written permission from the person being photographed, while the regulation of portrait commercialization in Law No. 28 the year 2014 concerning Copyright, permission or approval of the person being photographed is only limited to commercialization for advertising and billboards, even though there are economic benefits that the t-shirt seller gets from the sale of the t-shirt and in fact, the t-shirt sells because the buyer bought the t-shirt because of the artist's portrait. in the shirt. Paper type: Research paper